REVISED STRATIGRAPHY OF THE SERRA PALAZZO FORMATION, A MIOCENE FOREDEEP TURBIDITE SUCCESSION OF THE SOUTHERN APENNINES (ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
This paper illustrates a new structural and stratigraphical framework of the Serra Palazzo Formation which represents a Miocene turbidite succession cropping out at the outer border of the Southern Apennines. The study has been performed in the type area of the Serra Palazzo Formation, in the neighbourhood of Stigliano village (Basilicata, Southern Italy). Structural evidence allowed to recognise that in the study area the Serra Palazzo Formation has been splitted in different east verging thrust sheets whose decollement level is localized in the upper part of the Flysch Rosso Formation. The stratigraphical features of the study formation have been collected in two sections (S1 and S2) belonging to two superimposed thrust sheets; biostratigraphic analyses have been performed by means of quantitative methods on the calcareous nannofossil assemblages. The obtained results indicate that in the type area the Serra Palazzo Formation is about 500 m thick and from the bottom to the top consists of: a lower coarse grained siliciclastic turbidite unit (Tempa Cisterna Member), which lies stratigraphically on the Flysch Numidico Formation and is Burdigalian-Langhian in age; an upper siliciclastic and calciclastic fine grained turbidite unit (Jazzo Porcellini Member) that is Serravallian in age. The Jazzo Porcellini Member passes upward into the Marne argillose del Toppo Capuana Formation, of Serravallian-Tortonian age. The Tempa Cisterna Member, which has a north western feeding, reaches its maximun thickness (350 m) in the inner thrust sheet; on the contrary, the Jazzo Porcellini Member shows evidence of a consistent eastern supply and has its maximun thickness (250 m) in the outer thrust sheet. Preliminary studies suggest that the stratigraphical framework of the Serra Palazzo Formation as reconstructed in the study area can be also recognised in other areas of the Southern Apennines; these evidences provide new data on the evolution of the Southern Apennines Miocene foredeep.